1997
DOI: 10.1039/a607715c
|View full text |Cite
|
Sign up to set email alerts
|

Amperometric Bienzymic Sensor for Aspartame

Abstract: An amperometric enzyme electrode for the determination of aspartame was developed by covalent immobilization of alcohol oxidase and alpha-chymotrypsin. A platinum based hydrogen peroxide electrode was used as the detector. Excellent sensitivity was obtained using batch, flow-through and flow injection methods with detection limits of 2 x 10(-7), 4 x 10(-7) and 10(-6) mol l-1, respectively. Different strategies for eliminating interfering compounds, including the introduction of an additional alcohol oxidase-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 16 publications
0
7
0
2
Order By: Relevance
“…Only few papers describe biosensors for the determination of aspartame in soft drinks. Those biosensors were based on the chemical co-immobilization of enzymes on different electrodes, such as ammonia-gas-sensing electrode [18], platinum-based hydrogen peroxide electrode [19], oxygen electrode [20], or graphite epoxy composite electrode [21]. Another strategy is based on the enzyme immobilization into columns integrated in flow systems: two enzyme columns containing peptidase and aspartate aminotransferase, respectively, immobilized on activated aminopropyl glass beads and an L-glutamate oxidase electrode [22] or another system consisting of a column containing pronase and an L-amino acid oxidase electrode [23].…”
Section: Introductionmentioning
confidence: 99%
“…Only few papers describe biosensors for the determination of aspartame in soft drinks. Those biosensors were based on the chemical co-immobilization of enzymes on different electrodes, such as ammonia-gas-sensing electrode [18], platinum-based hydrogen peroxide electrode [19], oxygen electrode [20], or graphite epoxy composite electrode [21]. Another strategy is based on the enzyme immobilization into columns integrated in flow systems: two enzyme columns containing peptidase and aspartate aminotransferase, respectively, immobilized on activated aminopropyl glass beads and an L-glutamate oxidase electrode [22] or another system consisting of a column containing pronase and an L-amino acid oxidase electrode [23].…”
Section: Introductionmentioning
confidence: 99%
“…The performance of the amperometric enzyme electrode (Compagnone et al 1997), in terms of sensitivity, was superior to that of a previously reported aspartame biosensor and its detection limit was also lower than those achieved by spectrophotometric procedures, though a spectrophotometric procedure also provides a low detection limit (Fatibello-Filho et al 1999). The precision was similar in all the methods proposed, and always lower than 3.5% (relative standard deviation ).…”
Section: Aspartamementioning
confidence: 86%
“…The FIA biosensor was stable for at least 30 h of continuous use at room temperature (Male et al 1993). An aspartame electrode developed by covalent immobilization of alcohol oxidase and a-chymotrypsin (bovine pancreas) on the surf ace of a platinum-based hydrogen peroxide electrode was described by Compagnone et al (1997). The biosensor has been used for the measurement of aspartame with batch, ow-through and FI methods.…”
Section: Description Of the Methods According To The Detection Technimentioning
confidence: 99%
See 1 more Smart Citation
“…Biossensores envolvendo diferentes enzimas e técnicas de imobilização estão descritos na literatura [15][16][17][18][19][20][21] . Um biossensor contendo a L-aspartase 19 e outro contendo essa enzima co-imobilizada com a carboxipeptidase A 20 imobilizadas sobre uma membrana de um eletrodo sensível a amônia foram utilizados na determinação de aspartame em diversos produtos dietéticos.…”
unclassified